Quantitative image analysis of protein expression and colocalisation in skin sections. Issue 2 (9th January 2018) - Zhang, Hanqian; Ericsson, Maja; Virtanen, Marie; Weström, Simone; Wählby, Carolina; Vahlquist, Anders; Törmä, Hans
Abstract: Immunofluorescence (IF) and in situ proximity ligation assay ( is PLA) are techniques that are used for in situ protein expression and colocalisation analysis, respectively. However, an efficient quantitative method to analyse both IF and is PLA staining on skin sections is lacking. Therefore, we developed a new method for semi‐automatic quantitative layer‐by‐layer measurement of protein expression and colocalisation in skin sections using the free open‐source software CellProfiler. As a proof of principle, IF and is PLA of ichthyosis‐related proteins TGm‐1 and SDR9C7 were examined. The results indicate that this new method can be used for protein expression and colocalisation analysis in skin sections.